Understanding the impact of body changes in the key measurements used in pattern design and comfort of aged people - Carvalho, Miguel (2014)
The standards used by clothing manufacturers are defined for younger age group, disabling older people to be accommodated by the apparel industry. These misfit garment problems are generally due to the different body configurations brought by the aging process, causing dissatisfaction and frustration. There are very few garments available that were designed taking in consideration the older population anthropometrics. As such, it is important to understand the various measurements that characterize the senior population in order to produce more form-fitting garments. The objective of this paper is to perform a comparative analysis between the body dimension of younger and older people. Additionally, it is intended to create a base model for a mannequin that has the appropriate anthropometric dimensions to accommodate the older population.